Has Global Financial Reporting Comparability Improved?* - Conaway, Jenelle K. (Contemporary Accounting Research, 2022)
ABSTRACT Motivated by ongoing worldwide efforts to improve the comparability of accounting information, I examine the temporal trend in global financial reporting comparability. Regulators have made serious efforts to improve comparability, but numerous frictions may have limited their effectiveness. Accordingly, I examine the time‐series properties of comparability measures for a sample of the 36 largest economies and provide two key empirical insights consistent with expectations. First, I confirm comparability is increasing over 2002–2018. Second, I document that this increase primarily occurs in firms applying local accounting standards, as opposed to those applying global standards (defined as either US GAAP or IFRS). Additional analyses reveal that: (i) firms applying local standards are becoming more comparable to firms applying IFRS but not to those applying US GAAP, and (ii) comparability within global‐standards firms is not changing. I also document that certain market liquidity benefits of comparability are sustained in the long term, as firms increasing comparability over the sample period experience greater reductions in bid‐ask spread and zero‐return trading days relative to those decreasing comparability. Overall, the results reveal that comparability has increased—consistent with systematic regulatory efforts—but that this increase arises heterogeneously across firms, with the primary effects in recent years occurring among those applying local standards.